(untitled) (The Pakistan Development Review, 1987)
The phenomena of migration and fertility has not drawn much attention in Pakistan. A few studies based on census data, the National impact Survey 1968-69 and the Population Growth Survey 1968-71 showed higher crude birth rates for rural areas than for urban areas. However, recent studies showed higher urban fertility in Pakistan. In view of the increasing rate of rural migration to the urban areas it is important to understand the contribution of migration to population growth. The main objective of the present study is to explore differentials in fertility between migrants and non-migrants along with the socio-economic and proximate determinants and to investigate whether these show statistically significant variation in fertility between migrants and non-migrants. The primary source of data for this study is the Population Labour Force and Migration Survey (PLM) 1979-80. Migration and fertility questionnaires were merged to determine the migration status of husband and wife to relate it to the fertility of women. A total of 33S female migrants in urban areas and 480 in rural areas were identified.